Psychological Sequelae of COVID-19: The Mediating Role of Family Communication as a Protective Factor - Umaiza Bashir; Ayesha Jabeen (Aziz Fatimah Medical and Dental College, 2022)
Objectives: To assess the mediating role of family communication between the relationship of psychological strengths or sequelae and anxiety symptoms in general population during lockdown in COVID-19 among. Methodology: A cross-sectional research design was used to assess a sample of age range 18 years to 60 years during a period of March 2020- July 2020 after taking Ethical approval by a institutional review board of university. The measures of the study including demographic variables form, indigenous scale for Psychological Strengths and Depression Anxiety Stress Scale (DASS) was used to measure the anxiety in population. The Family Communication scale was used to measure the mediating effect of communication within family members. Using convenient sampling online google form was generate and from 371 participants' data was collected, in which adult general population was included. Result: The present study showed that there was a significant relationship between the study variables, and family communication indicated partial mediating role between psychological sequelae and anxiety symptoms. Conclusion: It can be concluded that to better deal with the anxiety related to corona virus disease positive perspective is important and family bonding and communication play significant role in increasing psychological strengths.